Predicting the potential distribution of the alien invasive American bullfrog (Lithobates catesbeianus) in Brazil - Giovanelli, Joao G. R. [UNESP]; Haddad, Celio Fernando Baptista [UNESP]; Alexandrino, Joao [UNESP] (Springer, 2008)
The non-native invasive anuran Lithobates catesbeianus is presently distributed in Brazil, especially in the Atlantic Rainforest biodiversity hotspot. Here, we use a maximum entropy ecological niche modeling algorithm (i) to model the North American native geographic distribution of this species and (ii) to project that model onto the whole of Brazil. After applying a threshold value that balances commission and omission errors, the projection results suggested high probabilities of occurrence mostly in southern and southeastern Brazil. We also present the first report on the species known distribution in Brazil, showing good agreement with model predictions. If the predictive map is interpreted as depicting invasiveness potential of L. catesbeianus, strategies to prevent further invasion in Brazil should be focused especially in the Atlantic Rainforest biodiversity hotspot.
Keywords: ecological modeling; exotic species; maxent; bioclim; anura; American bullfrog